Pneumoretroperitoneum, pneumomediastinum, and neck emphysema due to rectal diverticulosis - Floreta Kurti; Viola Cala; Gentian Vyshka (Clinical Case Reports, 2022)
Abstract Intestinal diverticulosis is a chronic disorder that might present with acute symptoms, due to colonic perforation. Pneumoperitoneum and air bubbles spreading in different anatomical locations can be seen. These complications need careful consideration and, when appropriate, surgery, for an otherwise chronic condition that can be successfully treated through conservative measures.